Innovative born globals: Investigating the influence of their business models on international performance - Kraus, Sascha; Brem, Alexander; Schuessler, Miriam; Schuessler, Felix; Niemand, Thomas (Managing Innovation: Internationalization Of Innovation, 2019)
Internationalization is a hot topic in innovation management, whereby the phenomenon of "Born Globals" is still limited to research in the domains of Entrepreneurship and International Management. As business model design plays a key role for Born Globals, we link these two concepts. For this, we propose hypotheses about the influence of efficiencycentered and novelty-centered business model design on international firm performance. To test these hypotheses, we performed a quantitative survey with 252 founders of international companies in Germany, Switzerland and Liechtenstein. Additionally, we gained further insights through a case study analysis of 11 Born Globals. The results show that business model design matters to international firm performance and the business model design of Born Globals tends to be more efficiency-centered. Based on a multiple case study, we analyzed business models in a more sophisticated way and derived propositions that yielded in an archetype of a Born Global's business model.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Born global; Business model; International new venture; International performance; Internationalization